2021
DOI: 10.1002/jclp.23261
|View full text |Cite
|
Sign up to set email alerts
|

Examining bereavement‐related needs and outcomes among survivors of sudden loss: A latent profile analysis

Abstract: Objective: Recognizing important bereavement-related needs among sudden loss survivors (e.g., suicide, overdose)-a population that is burgeoning and at risk for deleterious outcomes-is a critical task as needs may reflect modifiable grief-related variables that can assist with postloss adjustment. Methods: Latent profile analysis was used among 347 sudden loss survivors to (a) identify distinct patterns of needs among survivors of sudden loss, (b) assess predictors of such profiles, and (c) investigate differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Although these are the only studies that directly examine mental health correlates of overdose loss, these investigations were limited by a relatively small sample size, included drug-related deaths (e.g., deaths due to accident or infectious disease secondary to drug use), or failed to capture other forms of psychopathology (e.g., moodrelated symptoms and suicide risk) to provide a more accurate scope of the problem. Although not a direct examination of overdose loss survivorship, Bottomley et al (2021) examined patterns of bereavement-related needs and their associated outcomes among a sample of sudden loss survivors (i.e., overdose, suicide, and sudden natural losses). Four homogenous groups of individuals were identified based on the importance of needs with individuals reporting the highest degree of needs being predominately comprised of overdose BOTTOMLEY ET AL.…”
Section: The Phenomenology Of Opioid-related Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these are the only studies that directly examine mental health correlates of overdose loss, these investigations were limited by a relatively small sample size, included drug-related deaths (e.g., deaths due to accident or infectious disease secondary to drug use), or failed to capture other forms of psychopathology (e.g., moodrelated symptoms and suicide risk) to provide a more accurate scope of the problem. Although not a direct examination of overdose loss survivorship, Bottomley et al (2021) examined patterns of bereavement-related needs and their associated outcomes among a sample of sudden loss survivors (i.e., overdose, suicide, and sudden natural losses). Four homogenous groups of individuals were identified based on the importance of needs with individuals reporting the highest degree of needs being predominately comprised of overdose BOTTOMLEY ET AL.…”
Section: The Phenomenology Of Opioid-related Lossmentioning
confidence: 99%
“…Although not a direct examination of overdose loss survivorship, Bottomley et al. (2021) examined patterns of bereavement‐related needs and their associated outcomes among a sample of sudden loss survivors (i.e., overdose, suicide, and sudden natural losses). Four homogenous groups of individuals were identified based on the importance of needs with individuals reporting the highest degree of needs being predominately comprised of overdose and suicide loss survivors.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study suggest that the 20-item SBNI is a psychometrically valid and reliable instrument for assessing bereavement needs following sudden death by suicide, overdose, or natural causes-causes of death that are increasing in prevalence (Centers for Disease Control and Prevention, 2021) and are associated with a panoply of negative outcomes (e.g., Bottomley, Campbell, & Neimeyer, 2021;Rozalski et al, 2016). This study confirmed that the SBNI comprised six factors: Pragmatic Needs, Informational Needs, Spiritual Needs, Relational Needs, Meaning Needs, and Emotional Needs.…”
Section: Discussionmentioning
confidence: 95%
“…Parents who have experienced a drug-related bereavement have a higher mortality rate than non-bereaved parents and parents bereaved by other causes of death ( Christiansen et al, 2020 ). Bottomley et al (2021) studied the mental health burden associated with overdose-related deaths and found that the overall mental health burden of those bereaved by overdose is substantial compared to those bereaved by sudden natural loss. People bereaved by overdose were almost three times more likely to meet the symptom severity level for prolonged grief disorder (PGD), post-traumatic stress disorder, and major depressive disorder.…”
Section: Introductionmentioning
confidence: 99%
“…People bereaved by overdose were almost three times more likely to meet the symptom severity level for prolonged grief disorder (PGD), post-traumatic stress disorder, and major depressive disorder. They also appeared to be at risk of generalized anxiety disorder and suicide ( Bottomley et al, 2021 ). Titlestad and Dyregrov (2022) have also found a strong association between suicidal thoughts and high levels of PGD among bereaved family members, with the highest level of prolonged grief symptoms found among participants in the group who had lost a family member one to 2 years previously.…”
Section: Introductionmentioning
confidence: 99%